The Effectiveness of Using Interactive E-Books of Spending Plant Through Online Learning - Oktafiani, Rizka; Widiatningrum, Talitha; Retnoningsih, Amin (Journal of Innovative Science Education, 2021)
The seed plant e-book is an online learning solution. Efforts to improve the quality of learning resources for plantae material, mostly seed plants, are carried out by developing interactive e-books to support online learning. The interactive e-book is designed using a scientific and contextual approach. This study aimed to analyze the effectiveness of the interactive e-book on seed plants with a scientific and contextual approach to the learning outcomes of students. This research method is an experiment to measure the effectiveness of using e-books with a non-equivalent pretest-posttest control group research design to measure learning outcomes. The average of students' learning outcomes in the cognitive aspect is 90.41. The result of the N-Gain calculation of the average learning result or the concept mastery ability test of 0. 72 is included in the high category. Interactive e-books are proven to be effective in improving cognitive, affective, and psychomotor learning outcomes. The use of e-books in online learning encourages student-centered learning because, in the learning process, students are more active and do not depend on the teacher.